Evaluation of Morphological Characteristics and Fatty Acid Compositions of Some Local Varieties of Oil Flax - Osmani, Abdul Alim; Asim, Abdul Msawer; Danishyar, Eraj; Amin, Mohammad Wasif; Farid, Zabihullah; Joya, Khalid; Aminy, Hakimullah; Sarhadi, Wakil Ahmad (Journal for Research in Applied Sciences and Biotechnology, 2023)
Oil flax (Linum usitatissimum L.) is a valuable agricultural crop with potential uses in industries including oil production, nutrition, and medicine. It has a good reputation in Afghanistan as an oil crop. The objective of the current research was to compare the most significant morphological parameters and fatty acid compositions of some local oilflax. The study used a randomized complete block design and was conducted on the research and experimental farm of Parwan University's (REFPU) Faculty of Agriculture in Parwan, Afghanistan, during the 2022 growing season. In this experiment, four seed samples from various regions of Afghanistan [Parwan (V1), Badakhshan (V2), Baghlan (V3), and Kunduz (V4)] were used. The results showed no significant difference between the local varieties on all growth parameters except for the number of seeds per capsule (NSC) and the weight of a thousand seeds (WTS). The maximum NSC was significantly observed in the V1 (10.8), followed by the V3 (7.13) and the V4 (7.33), and the lowest was recorded in the V2 (6.7). The heaviest WTS were significantly produced by V1 (9 gr) compared to V2 (4.67 gr), V3 (5.67 gr), and V4 (4.67 gr). Also, there was not a noticeable difference in the concentration of linoleic acid (LA) and linolenic acid (LLA) between the varieties. Each of the studied local varieties can be used because of their similar performance.